Outcomes following operative vs. non-operative management of blunt traumatic pancreatic injuries: a retrospective multi-institutional study. Issue 1 (9th December 2016) - Addison, Poppy; Iurcotta, Toni; Amodu, Leo I.; Crandall, Geoffrey; Akerman, Meredith; Galvin, Daniel; Glazer, Annemarie; Christopherson, Nathan; Prince, Jose; Bank, Matthew; Sorrentino, Christopher; Cagliani, Joaquin; et al.
Abstract: Background: Traumatic pancreatic injuries are rare, and guidelines specifying management are controversial and difficult to apply in the acute clinical setting. Due to sparse data on these injuries, we carried out a retrospective review to determine outcomes following surgical or non-surgical management of traumatic pancreatic injuries. We hypothesize a higher morbidity and mortality rate in patients treated surgically when compared to patients treated non-surgically. Methods: We performed a retrospective review of data from four trauma centers in New York from 1990–2014, comparing patients who had blunt traumatic pancreatic injuries who were managed operatively to those managed non-operatively. We compared continuous variables using the Mann-Whitney U test and categorical variables using the chi-square and Fisher's exact tests. Univariate analysis was performed to determine the possible confounding factors associated with mortality in both treatment groups. Results: Twenty nine patients were managed operatively and 32 non-operatively. There was a significant difference between the operative and non-operative groups in median age (37.0 vs. 16.2 years, P = 0.016), grade of pancreatic injury (grade I; 30.8 vs. 85.2%, P value for all comparisons <0.0001), median injury severity score (ISS) (16.0 vs. 4.0, P = 0.002), blood transfusion (55.2 vs. 15.6%, P = 0.0012), other abdominal injuries (79.3 vs. 38.7%, P = 0.0014), pelvic fractures (17.2 vs. 0.00%, P = 0.020), intensive care unit (ICU) admission (86.2 vs. 50.0%, P = 0.003), median length of stay (LOS) (16.0 vs. 4.0 days, P <0.0001), and mortality (27.6 vs. 3.1%, P = 0.010). Conclusions: Patients with traumatic pancreatic injuries treated operatively were more severely injured and suffered greater complications than those treated non-operatively. The greater morbidity and mortality associated with these patients warrants further study to determine optimal triage strategies and which subset of patients is likely to benefit from surgery.